Social Change and Health Policy in Venezuela - Carlos H. Alvarado; María E. Martínez; Sarai Vivas-Martínez; Nuramy J. Gutiérrez; Wolfram Metzger (Social Medicine Publication Group, 2008)
This work reviews social changes occurring in Venezuela during the last two decades, examining how they led to the development of a new health policy. Initially, the political context of the nineties is examined; this was a time when the neoliberal politics of the 1980's had a demonstrable impact on the living conditions and health status of the population. By 1999 social and political events led to a new Constitution which provided the juridical and legal framework for a new health policy. The conceptualization of health and the model of health care which arose from the constitutional process are considered, as well as the reaction of the dominant economic and political sectors to the new policies imposed by constitutional mandate. The emergence of Barrio Adentro and other social missions is analyzed as an essential factor in the initiation of structural changes within the country and its health institutions. The Barrio Adentro program is described in detail, along with key steps in the development of the Venezuelan National Public Health System. Finally, the impact of these new health policies on the quality of life of the Venezuelan population is delineated.